Peran Teknologi Dalam Pengajaran Bahasa Inggris Modern (Elt) - Junaidi Rahman (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
This study aims to explore students' perceptions of the use of technology in English language learning at SDN 1 Janapria 5th grade. Using a descriptive quantitative approach, data was obtained through a Likert scale-based questionnaire and interviews with teachers. Results show that the majority of students have a very positive perception of the application of technology, with an average score above 4 for each indicator. Technology-based learning media such as videos, interactive quizzes, and online applications are considered capable of increasing students' interest, understanding, and motivation in learning English. However, there are still barriers such as limited access to devices and internet networks. This research confirms the important role of technology as a strategic supporting tool in English Language Teaching (ELT), as well as the need for infrastructure support and teacher training to optimize digital learning.